PERSEPSI MASYARAKAT SURABAYA TERHADAP PERENCANAAN DANA PENSIUN - Mellisa Marcellina Gunawan; Andrew Darrent; Amelia Feliciana Ticoalu; Njo Anastasia (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Retirement planning is an important thing to do for every individual. Individuals who do not have a good retirement plan are feared to have anxiety about their retirement. This research is a basic research that examines the perception of the people of Surabaya on retirement planning qualitatively. This study uses the Theory of Planned Behavior (TPB), Time Discounting, and Proactivity variables as triggers for a person’s intention to plan for retirement. This study aims to determine the Surabaya people's perception of retirement planning and what factors influence an individual to decide to do financial planning. The research was conducted by conducting in - depth interviews with several resource persons with active working criteria, in which the results of the interviews would be used as material for further discussion. It was found from the discussions that several factors in the TPB, Time Discounting, and Proactivity indirectly influenced the intentions of the informants.